Pooled Multicenter Safety Analysis of Lupin’s Intravitreal Biosimilar Ranibizumab (Ranieyes) in Chorioretinal Vascular Diseases - Debdulal Chakraborty; Tushar Kanti Sinha; Sourav Sinha; Aniruddha Maiti; Angshuman Mukherjee; Krishnendu Nandi; Sudipta Das; Saptorshi Majumdar; Dinesh Rungta; Ranabir Bhattacharya (Ophthalmology and Therapy)
Abstract Introduction This study aims to evaluate the ocular and systemic safety profiles of intravitreal biosimilar ranibizumab Ranieyes (Lupin Pharmaceuticals, Mumbai, India) in real-world clinical settings across multiple chorioretinal vascular diseases, including neovascular age-related macular degeneration (nAMD), diabetic macular edema (DME), and retinal vein occlusion (RVO) in adults. Methods We conducted a retrospective, consecutive, interventional, uncontrolled multicenter study using data from three hospital networks in India. A total of 1401 eyes received 2194 injections of Ranieyes between June 2022 and November 2023. Patients were followed for a minimum of 6 months, and data on ocular and systemic adverse events (AEs) were collected and analyzed. Results The study population included 636 male patients and 533 female patients, with a mean age of 58.63 ± 11.54 years. The average number of injections per eye was 1.49 ± 0.23, with the highest frequency in the nAMD group (mean of 2.3 ± 0.23 injections per eye) over 6 months. Non-serious adverse events (nsAEs) were observed in 26.83% of injections, with mild ocular pain and transient blurring of vision being the most common. Serious ocular adverse events were rare, occurring in 0.85% of eyes, with retinal pigment epithelial tear (RPE TEAR) being the most frequent. Systemic adverse events were noted in 5.03% of patients, and all but one were non-serious. One patient developed non-fatal myocardial infarction, the causal relationship of which, however, was not established with the intravitreal agent used. No cases of endophthalmitis were observed. Conclusions This large-scale, real-world study demonstrates that Ranieyes is a safe intravitreal antivascular endothelial growth factor (anti-VEGF) agent across various chorioretinal vascular diseases. The safety profile of Ranieyes is consistent with that of the reference product, making it a viable option in resource-constrained settings.